On Stockhausen’s Kontakte (1959-60) for tape, piano and percussion: A lecture/analysis by John Rea given at the University of Toronto, march 1968 - Rea, John (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2009)
Abstract A lecture/analysis given by John Rea at the University of Toronto, March 1968, discusses various topics in the composition such as: concepts (performance time, production time, subjective perception of time, moment time, moment characteristics), discussion of particular Moments, hardware, overall formal organization, definition of structure, parameter of space (an example), temporal transformation, and performance practice. The lecture text is also notable for the fact that Rea spoke to the pianist who had premiered Kontakte, David Tudor, who was in Toronto at that time to participate in a four and a half hour ‘happening’ known as Reunion (on March 5, 1968) organized by John Cage, and featuring Marcel Duchamp with whom he played chess on a photo-sensitive electronic chessboard.